Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy di Dealer Surya Mandala Jambi - Angellia Kharisman (Universitas Batanghari Jambi, 2020)
The purpose of this research is to find out the influence of location and promotion in consumer decisions in buying Honda Scoopy. The method used is quantitative by using primary and secondary, the method of data collection is taken from library research and field research with a population that includes all consumers who buy Honda Scoopy at Surya Mandala Jambi Dealer and used 100 research samples. The analysis method in this study is descriptive with the analysis tools used multiple linear equations, classic assumption tests and hypothesis tests. From the results of Multiple Linear Regression Y = 0.682 + 0.118X1 + 0.421X2 there is a positive influence between the relationship of promotion variables, location and purchasing decisions.